2001
DOI: 10.1136/hrt.86.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Long axis excursion in aortic stenosis

Abstract: OBJECTIVESTo examine long axis excursion in patients with all grades of aortic stenosis and preserved transverse systolic function, and to compare long axis excursion in symptomatic with that in asymptomatic severe aortic stenosis.DESIGNProspective comparative study.SETTINGRegional cardiothoracic centre.PATIENTS78 patients with all grades of aortic stenosis and normal fractional shortening and ejection fraction were studied. There were two comparison groups, 10 age matched normal subjects and 14 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…30,31 Previous studies have shown that a reduction in LV longitudinal function occurs simultaneously with AS progression, even in patients with moderate AS, providing evidence of impaired LV longitudinal strain despite normal LVEF in patients with significant AS. 32,33 In addition, Weidemann et al 15 demonstrated that markers of LV systolic longitudinal function are associated with the severity of myocardial fibrosis in patients with significant AS. On the basis of these studies, the development of LV myocardial fibrosis seems to be one of the main pathophysiologic mechanisms to explain a reduction in LV systolic longitudinal function in patients with significant AS.…”
Section: Pathophysiology Of LV Gls In Moderate Asmentioning
confidence: 99%
“…30,31 Previous studies have shown that a reduction in LV longitudinal function occurs simultaneously with AS progression, even in patients with moderate AS, providing evidence of impaired LV longitudinal strain despite normal LVEF in patients with significant AS. 32,33 In addition, Weidemann et al 15 demonstrated that markers of LV systolic longitudinal function are associated with the severity of myocardial fibrosis in patients with significant AS. On the basis of these studies, the development of LV myocardial fibrosis seems to be one of the main pathophysiologic mechanisms to explain a reduction in LV systolic longitudinal function in patients with significant AS.…”
Section: Pathophysiology Of LV Gls In Moderate Asmentioning
confidence: 99%
“…The alteration of LV longitudinal function occurs in parallel to AS severity (19), LV morphological changes (20), LV myocardial damage and fibrosis proliferation (11). Weidemann et al (11) reported that the severity of myocardial fibrosis estimated with histological analysis was associated with impairment of LV longitudinal shortening as assessed by mitral annulus displacement using M-mode echocardiography.…”
Section: Longitudinal Function and Myocardial Fibrosismentioning
confidence: 99%
“…[20,21] In addition, impairment of LV longitudinal shortening or strain correlates with the presence of symptoms in patients with AS, is associated with LV myocardial fibrosis by cardiac Magnetic Resonance Imaging (cMRI) and predicts elicited symptoms during exercise testing in the subset of asymptomatic patients able to exercise. [22][23][24][25][26] Hence, the assessment of LV GLS may be helpful to identify patients with severe AS who present significant myocardial damage and who are at higher risk, despite preserved LVEF and no or only mild symptoms.…”
Section: Dysfunction In Asmentioning
confidence: 99%